A Note on Socialist Economics - Lerner, A. P. (Review of Economic Studies, 1936)
Journal Article A Note on Socialist Economics Get access A. P. Lerner A. P. Lerner London School of Economics Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 4, Issue 1, October 1936, Pages 72–76, https://doi.org/10.2307/2967661 Published: 01 October 1936